Moderate Nitrogen Application Synergistically Improved Yield and Quality of Nanjing Series japonica Rice Varieties with Good Taste - Xiaodong Wei; Qingyong Zhao; Chunfang Zhao; Yong Zhang; Tao Chen; Zhen Zhu; Kai Lu; Lei He; Lihui Zhou; Shengdong Huang; Yusheng Li; Wang Cailin; et al. (Plants)
Nanjing series japonica rice varieties developed by the Institute of Food Crops, Jiangsu Academy of Agricultural Sciences in China have the characteristics of an excellent taste quality, high yield, and good resistance. They are widely promoted and applied in the lower reaches of the Yangtze River in China’s japonica rice planting areas. In response to the problem of the lack of coordination between nitrogen fertilizer management measures and variety characteristics in production, which makes it difficult to synergistically improve yield and quality, this study adopted a split-plot experimental design to study the effect of nitrogen fertilizer application on yield and rice quality of Nanjing series japonica rice varieties. In 2021, four nitrogen application rates of 0 (N1), 150 (N2), 300 (N3), and 450 (N4) kg hm−2 (all pure nitrogen) were set up, and in 2022, four treatments of 120 (N1), 180 (N2), 240 (N3), and 300 (N4) kg hm−2 were set up, all with nitrogen application rate as the main plot factor and variety as the sub-plot factor. The results showed that the differences between the different nitrogen fertilizer treatments were significant at the 5% or 1% level, except for the milled rice rate, head rice rate, peak viscosity, setback viscosity, and paste temperature in 2021 and panicle number, grain number per panicle, all Rapid Visco-analyzer (RVA) characteristic values, and amylose content in 2022. With an increase in the nitrogen application rate, the number of panicles, grain number per panicle, and yield increased. Either the rates of brown rice, milled rice, or head rice and chalky grains or chalkiness showed an increase trend. The peak viscosity, hot viscosity, final viscosity, and breakdown viscosity decreased, while the setback viscosity increased. For the quality of cooked rice, the hardness increased, appearance, viscosity, and balance decreased, protein content increased, and taste value decreased. The interaction between nitrogen application rate and variety was significant at p < 0.05 or p < 0.01 only for yield components, processing quality, and rice protein content in 2021 and for eating and cooking quality, appearance quality, and peak viscosity in 2022. Other traits were not significant. The comprehensive results from two years of experiments showed that, under the conditions of this experiment, a nitrogen application rate of 240–300 kg hm−2 could improve the quality of rice in the Nanjing series varieties while maintaining a high yield. The results of this experiment have a guiding significance for the high-yield and high-quality cultivation of excellent-tasting Nanjing series japonica rice.